Association between intention to leave work and quality of work-life of Saudi pharmacists - Nouf Algazlan; Ahmed Al-jedai; Abdulrahman Alamri; Ahmed M. Alshehri; Lames Aldaiji; Yasser Almogbel (Saudi Pharmaceutical Journal, 2022)
Background/Aim: Pharmacists are one of the most essential healthcare professionals, with substantial clinical knowledge and skills in the use of medications. Pharmacists provide patient care services and contribute to the enhancement of health outcomes, which increases their workload. This study was conducted to determine the association between intention to leave work and quality of work life (QWL) of pharmacists in Saudi Arabia. Methods: This cross-sectional study was conducted using a self-administered questionnaire provided as a paper-based survey using two scales (the Work-related Quality of Life [QoL] and Intention to Leave scales). In addition, this was combined with demographics to determine the relationship between intention to leave work and quality of work-life. Data were analyzed using descriptive and analytical statistical tests. Results: A total of 284 (76.5%), out of the 371 surveys distributed, were completed and returned. The average age and annual income of the respondents were 33.4 ± 6.5 years and 196,401 ± 82,306.7 SAR, respectively and 61.2% and 38.9% were male and female, respectively, whereas 62.9% were married and 53.2% reported having children. The multiple linear regression analysis conducted showed a significant negative relationship between QWL and the intention to leave work (β = -0.131; 95% CI, −0.185 to −0.076). Conclusion: We found a significant association between the QWL and intention to leave. This indicates that a greater intention to leave was associated with a low or lousy QWL among Saudi pharmacists.